Mobile Phone Panel Surveys in Developing Countries : A Practical Guide for Microdata Collection - Dabalen, Andrew; Etang, Alvin; Hoogeveen, Johannes; Mushi, Elvis; Schipper, Youdi; von Engelhardt, Johannes (Washington, DC: World Bank, 2016)
Household survey data are very useful for monitoring living conditions of citizens of any country. In developing countries, a lot of this data are collected through “traditional” face-to-face household surveys. Due to the remote and dispersed nature of many populations in developing countries, but also because of the complex nature of many survey questionnaires, collection of timely welfare data has often proved expensive and logistically challenging. Yet, there is a need for faster, cheaper to collect, lighter, more nimble data collection methods to address data gaps between big household surveys. The recent proliferation of mobile phone networks has opened new possibilities.